Virtual Mobility and the Lonely Cloud: Theorizing the Mobility‐Isolation Paradox for Self‐Employed Knowledge‐Workers in the Online Home‐Based Business Context. (8th December 2017) - Daniel, Elizabeth; Di Domenico, MariaLaura; Nunan, Daniel
Abstract: We advance both mobility and paradox theorizing by advocating the new concepts of 'mobility‐isolation paradox' and 'paradoxical imagination'. These emerged from examining the nuanced, multifaceted conceptualizations of the mobility‐isolation tensions facing home‐based, self‐employed, online knowledge‐workers. We thereby enhance current conceptual understandings of mobility, isolation and paradox by analyzing knowledge‐workers' interrelated, multidimensional experiences within restrictive home‐based working contexts. We compare the dearth of research and theorizing about these autonomous online knowledge‐workers with that available about other types of knowledge‐workers, such as online home‐based employees, and the more physically/corporeally mobile self‐employed. This research into an increasingly prevalent knowledge‐worker genre addresses these knowledge gaps by analyzing home‐based knowledge‐workers' views, and tensions from paradoxical pressures to be corporeally mobile and less isolated. Despite enjoying career, mental and virtual mobility through internet‐connectedness, they were found to seek face‐to‐face social and/or professional interactions, their isolation engendering loneliness, despite their solitude paradoxically often fostering creativity and innovation.